2018
DOI: 10.1016/j.drugalcdep.2018.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electronic cigarette liquid solvents propylene glycol and vegetable glycerin on user nicotine delivery, heart rate, subjective effects, and puff topography

Abstract: PG:VG ratio influenced nicotine delivery, some subjective effects, and puff topography. Lower overall product satisfaction associated with the 100PG liquid suggests factors other than nicotine delivery (e.g., aerosol visibility) may play a role in maintaining ECIG use. Regulating ECIG acute effects such as nicotine delivery and subjective effects may require simultaneous attention to liquid PG:VG ratio as well as device, liquid, and behavioral factors known to influence these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 161 publications
(355 reference statements)
4
64
0
Order By: Relevance
“…In addition, to the extent that nicotine form modifies sensory experience, it may also influence puffing and inhalation behavior and therefore exposure. For example, previous studies have shown that users modified their puffing behavior (i.e., lower puff duration and volume) when using PG instead of VG-based liquids, likely due to sensory experience 18 . We speculate that nicotine form may play a similar role; for example, users may decrease puffing intensity when using free-base nicotine, and thereby obtain less nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to the extent that nicotine form modifies sensory experience, it may also influence puffing and inhalation behavior and therefore exposure. For example, previous studies have shown that users modified their puffing behavior (i.e., lower puff duration and volume) when using PG instead of VG-based liquids, likely due to sensory experience 18 . We speculate that nicotine form may play a similar role; for example, users may decrease puffing intensity when using free-base nicotine, and thereby obtain less nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Devices were categorized into four groups consistent with previous research : (1) ‘cig‐a‐likes’, small cylindrical devices resembling combustible cigarettes with non‐refillable liquid cartridges; (2) ‘fixed‐power tanks’, devices with refillable tanks and no user‐adjustable power parameters; (3) ‘variable‐power tanks’, similar to fixed‐power devices but with the ability to change power parameters (e.g. voltage or wattage); and (4) ‘pods’, devices utilizing disposable pods with nicotine salt liquids.…”
Section: Methodsmentioning
confidence: 99%
“…Nicotine doses from e-cigarettes vary tremendously depending on characteristics of the user (experience with smoking conventional cigarettes or ecigarettes), technical aspects of the e-cigarette, and levels of nicotine in the e-liquid. Although studies of nicotine doses in youth and young adults are lacking, studies of adults have found delivery of nicotine from e-cigarettes in doses ranging from negligible to even larger than conventional cigarettes [5][6][7]. Nicotine dosing studies are necessary to compare relative toxicity among the different delivery systems.…”
Section: Electronic Cigarettes (E-cigarettes)mentioning
confidence: 99%